LAYANAN PADA ANAK USIA DINI ( Studi Kasus di TPA Beringharjo Yogyakarta ) - Nur Hidayah * (Dimensia: Jurnal Kajian Sosiologi, 2008)
The aim of this research is to learn about the profile of Beringharjo Childcare, service offered for early-age child at Beringharjo Childcare, early-age child model of service, the application process of early-age child service program, supporting factors and the obstacles in applying the early-age child service program. Moreover, the research also learns about the viewpoint of the people running the childcare on precise education urgency for early-age child, quality of employees, professionalism in running the early-age child service program, proportion of early-age child development aspects service, and people’s responses in making use of the service offered. This research is using the qualitative approach where data are collected by using the methods of interview, observation, and documentation. Data is analyzed by using data reduction where the data then served and concluded (verified) qualitatively. The research took place at Beringharjo Childcare, Yogyakarta. The results of this research, which took place at Beringharjo Childcare, are as follow: 1) It offers not only baby/child-sitting but also routine health check-up and guidance in corporation with Gondomanan Sub district’s Health Service Center. 2) The model of service offered is given in defined time however extra time will also be considered. 3) The process of applying the program is based on the same schedule for all children. Every child has the opportunity to draw, to color, learn numbers and alphabets. Children are allowed to play only in certain time. 4) The supporting factors on running this childcare still need to be improved whereas the obstacles still need to be evaluated for a better service. 5) More efforts are still needed in order to maintain the supporting factors and overcome the obstacles. 6) The viewpoint of persons running this childcare on precise education urgency for early-age child is still lack. 7) The proportion of service given by the childcare is considered still lack due to only emphasize on the motoric aspect where the child-minder do not aware on the urgency. 8) The response on the service offered by the childcare is good which can be seen on the number of children entrusted by parents in this childcare and how parents are helped. Keywords: service, early-age child, childcare